Predictors of postpartum return to smoking: a systematic review - Orton, Sophie; Coleman, Tim; Coleman-Haynes, Tom; Ussher, Michael (Oxford University Press, 2017)
Background: Finding effective ways to help pregnant women quit smoking and remain abstinent is a major public health issue. Approximately half of UK women who smoke attempt cessation after conception; unfortunately, up to 75% return to smoking within 12 months postpartum. Interventions for preventing postpartum return to smoking (PPRS) have not been found to be effective. It is important to identify factors associated with PPRS, to inform development of alternative interventions. Aim: Identify by systematic review factors associated with PPRS. Methods: Systematic searches of electronic databases (MEDLINE, EMBASE, PsychINFO, CINAHL), trials registers, and conference proceedings were conducted to November 2016. Studies statistically examining factors associated with PPRS were included. Modified versions of the Newcastle Ottawa Quality Assessment Scale were used to assess studies’ quality and a narrative synthesis focused on those judged of high quality. Results: Thirty-nine studies (12 trials, 27 observational studies) were included. Thirty-one (79.5%) studies were high-quality. Among these, the most common significant predictors of PPRS were being less well educated, younger, multiparous, living with a partner or household member who smoked, experiencing higher stress, depression or anxiety, not breastfeeding, intending to quit only for pregnancy and low confidence to remain abstinent postpartum. Conclusions: Of the factors found to be associated with PPRS, intending to quit smoking only for the duration of pregnancy, partner/household member smoking and confidence to remain abstinent are those most likely to have a direct, causal impact on smoking behavior after childbirth, and need to be considered when designing interventions to prevent PPRS. Implications: This is the first systematic review of factors that may facilitate or inhibit PPRS. Considering how having a partner or household member who smokes, intending to quit smoking only for pregnancy, having self-efficacy to quit long term, breastfeeding and depression exert direct or indirect impacts on women’s relapse to smoking and how such impacts could successfully be manipulated will inform development of new interventions to prevent PPRS.